(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This paper explores the integration of multiplatform digital tools into Uzbekistan’s public health policies as an innovative strategy to encourage active living and improve population health outcomes. As sedentary lifestyles and chronic diseases increase worldwide, digital health interventions have become essential tools for promoting physical activity and preventive behavior. The study examines how multiplatform technologies—including mobile fitness applications, wearable devices, web portals, and social media platforms—can enhance citizen engagement, provide real-time health monitoring, and support data-driven policymaking. By analyzing international experiences and current initiatives in Uzbekistan, the paper proposes a conceptual framework for embedding digital platforms into national health strategies. Findings highlight that government-supported digital ecosystems, when designed inclusively and with cultural adaptation, can significantly influence public motivation toward active living.